WAVE CLIMATE CHARACTERISTICS AND THE EFFECT OF TROPICAL CYCLONES ON HIGH WAVE OCCURRENCE IN INDONESIAâS FISHERIES MANAGEMENT AREAS (IFMA) - Azhari, Ainun
Utilization of fisheries management in Indonesian waters is divided into 11 areas, called IFMA (Indonesia’s Fisheries Management Areas). It is important to know the wind and wave climate characteristics in each IFMA to ensure safe and smooth fishery management activities. This study aims to determine the wave climate characteristics and the effect of tropical cyclone on high wave (SWH ? 2 m) occurrences in each IFMA. Wind and wave data are taken from European Center for Mediun-Range Weather Forecast (ECMWF), namely ECMWF Reanalysis v5 (ERA5). Tropical cyclones event data taken from International Best Track Archive for Climate Stewardship (IBTrACS) belongin to the National Oceanic and Atmospheric Administration (NOAA). The data period used is 42 years (1979–2020). The main methods in this research are descriptive and inferential statistics. The highest average of Significant Wave Height (SWH) occurred in IFMA that located in northern Indonesian waters during December–February (DJF), while IFMA in southern and inner Indonesian waters occured in June–August (JJA). The highest probability of exceedance on high waves occurrence is located in IFMA 573 (south Java) and reaches its maximum value in JJA (81.75%). There is increased of probability of exceedance value on high waves occurrence due to tropical cyclones that form in: (1) Bay of Bengal: IFMA 711 (DJF) and 572 (March–May, MAM); (2) west Pacific Ocean: IFMA 717 (DJF); (3) northeast Indian Ocean: IFMA 572 (DJF); last is in (4) west and north of Australia: IFMA 573 and 718 (DJF), also 711 (September–November, SON).